Social Proximity and the Erosion of Norm Compliance - Cristina Bicchieri; Eugen Dimant; Simon Gächter; Daniele Nosenzo (Institute of Labor Economics (IZA), 2020)
We study how individuals' compliance with norms of pro-social behavior is influenced by other actors' compliance in a novel, dynamic, and non-strategic experimental setting. We are particularly interested in the role that social proximity among peers plays in eroding or upholding norm compliance. Our results suggest that social proximity is crucial. In settings without known proximity, norm compliance erodes swiftly because participants only conform to observed norm violations of their peers while ignoring norm compliance. With known social proximity, participants conform to both types of observed behaviors, thus halting the erosion of norm compliance. Our findings stress the importance of the broader social context for norm compliance and show that, even in the absence of social sanctions, compliance can be sustained in repeated interactions, provided there is group identification, as is the case in many social encounters in natural and online environments.
Keywords: C92; D64; D9; 330; norm compliance; social norms; social proximity